Electro-optic steering of random laser emission in liquid crystals - Assanto, Gaetano; Perumbilavil, Sreekanth; Piccardi, Armando; Kauranen, Martti (Photonics Letters of Poland, 2018)
Using an external low-frequency electric field applied to dye-doped nematic liquid crystals, we demonstrate that random lasing obtained by optical pumping can be steered in angular direction by routing an all-optical waveguide able to collect the emitted light. By varying the applied voltage from 0 to 2 V, we reduce the walk-off and sweep the random laser guided beam over 7 degrees. Full Text: PDF References V. S. Letokhov, "Generation of light by a scattering medium with negative resonance absorption," Sov. Phys. JETP 26 (4), 835 (1968). DirectLink H. Cao, J. Y. Xu, D. Z. Zhang, S.-H. Chang, S. T. Ho, E. W. Seelig, X. Liu, and R. P. H. Chang, "Spatial Confinement of Laser Light in Active Random Media," Phys. Rev. Lett. 84 (24), 5584 (2000). CrossRef D. S. Wiersma, "The physics and applications of random lasers," Nature Phys. 4 (5) 359-367 (2008). CrossRef D. Wiersma and S. Cavalieri, "A temperature-tunable random laser," Nature 414, 708-709 (2001). CrossRef G. Strangi, S. Ferjani, V. Barna, A. De Luca, N. Scaramuzza, C. Versace, C. Umeton, and R. Bartolino, "Random lasing and weak localization of light in dye-doped nematic liquid crystals," Opt. Express 14 (17), 7737 (2006). CrossRef G. Strangi, S. Ferjani, V. Barna, A. De Luca, C. Versace, N. Scaramuzza, and R. Bartolino, "Random lasing in dye doped nematic liquid crystals: the role of confinement geometry," SPIE 6587, 65870P (2007) doi: 10.1117/12.722887 CrossRef S. Ferjani, V. Barna, A. De Luca, C. Versace, and G. Strangi, "Random lasing in freely suspended dye-doped nematic liquid crystals," Opt. Lett. 33(6), 557-559 (2008). CrossRef S. Ferjani, L-V. Sorriso, V. Barna, A. De Luca, R. De Marco, and G. Strangi, "Statistical analysis of random lasing emission properties in nematic liquid crystals," Phys. Rev. E 78 (1) 011707 (2008). CrossRef H. Bian, F. Yao, H. Liu, F. Huang, Y. Pei, C. Hou, and X. Sun, "Optically controlled random lasing based on photothermal effect in dye-doped nematic liquid crystals," Liq. Cryst. 41 (10), 1436-1441 (2014) CrossRef C. R. Lee, S. H. Lin, C. H. Guo, S. H. Chang, T. S. Mo, and S. C. Chu, "All-optically controllable random laser based on a dye-doped polymer-dispersed liquid crystal with nano-sized droplets," Opt. Express 18 (3), 2406-2412 (2010) CrossRef S. Perumbilavil, A. Piccardi, O. Buchnev, M. Kauranen, G. Strangi, and G. Assanto, "Soliton-assisted random lasing in optically-pumped liquid crystals," Appl. Phys. Lett. 109(16), 161105 (2016); ibid. 110(1), 1019902 (2017). CrossRef S. Perumbilavil, A. Piccardi, O. Buchnev, M. Kauranen, G. Strangi, and G. Assanto, "All-optical guided-wave random laser in nematic liquid crystals", Opt. Express 25 (5), 4672-4679 (2017). CrossRef S. Perumbilavil, A. Piccardi, R. Barboza, O. Buchnev, M. Kauranen, G. Strangi, and G. Assanto, "Beaming random laser with soliton control," Nature Comm., in press (2018) CrossRef M. Peccianti, C. Conti, G. Assanto, A. De Luca and C. Umeton, "Routing of Anisotropic Spatial Solitons and Modulational Instability in liquid crystals," Nature 432, 733-737 (2004). CrossRef J. Beeckman, K. Neyts and M. Haeltermann, "Patterned electrode steering of nematicons," J. Opt. A - Pure Appl. Opt. 8 (2), 214-220 (2006). CrossRef A. Piccardi, M. Peccianti, G. Assanto, A. Dyadyusha and M. Kaczmarek, "Voltage-driven in-plane steering of nematicons," Appl. Phys. Lett. 94, 091106 (2009). CrossRef R. Barboza, A. Alberucci, and G. Assanto, "Large electro-optic beam steering with Nematicons", Opt. Lett. 36 (14), 2611–2613 (2011). CrossRef A. Piccardi, A. Alberucci, R. Barboza, O. Buchnev, M. Kaczmarek, and G. Assanto, "In-plane steering of nematicon waveguides across an electrically adjusted interface", Appl. Phys. Lett. 100 (25), 251107 (2012). CrossRef Y. V. Izdebskaya, "Routing of spatial solitons by interaction with rod microelectrodes," Opt. Lett. 39(6), 1681-1684 (2014). CrossRef A. Pasquazi, A. Alberucci, M. Peccianti, and G. Assanto, "Signal processing by opto-optical interactions between self-localized and free propagating beams in liquid crystals," Appl. Phys. Lett. 87, 261104 (2005). CrossRef S. V. Serak, N. V. Tabiryan, M. Peccianti and G. Assanto, "Spatial Soliton All-Optical Logic Gates", IEEE Photon. Technol. Lett. 18 (12), 1287-1289 (2006). CrossRef M. Peccianti, C. Conti, G. Assanto, A. De Luca and C. Umeton, "All Optical Switching and Logic Gating with Spatial Solitons in Liquid Crystals," Appl. Phys. Lett. 81(18), 3335-3337 (2002). CrossRef A. Fratalocchi, A. Piccardi, M. Peccianti and G. Assanto, "Nonlinearly controlled angular momentum of soliton clusters," Opt. Lett. 32(11), 1447-1449 (2007). CrossRef Y. Izdebskaya, V. Shvedov, G. Assanto, and W. Krolikowski, Nat. Comm. 8, 14452 (2017). CrossRef M. Peccianti and G. Assanto, "Nematicons," Phys. Rep. 516, 147-208 (2012). CrossRef Y. Izdebskaya, A. Desyatnikov, G. Assanto and Y. Kivshar, "Deflection of nematicons through interaction with dielectric particles," J. Opt. Soc. Am. B 30(6), 1432-1437 (2013). CrossRef U. Laudyn, M. Kwasny, F. Sala, M. Karpierz, N. F. Smyth, and G. Assanto,"Curved solitons subject to transverse acceleration in reorientational soft matter," Sci. Rep. 7, 12385 (2017). CrossRef A. Alberucci, A. Piccardi, M. Peccianti, M. Kaczmarek and G. Assanto, "Propagation of spatial optical solitons in a dielectric with adjustable nonlinearity", Phys. Rev. A 82, 023806 (2010). CrossRef